The Strategy of School Heads in Improving the Discipline of Education Manpower in Madrasah - Jepri Husin (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The purpose of this study was to determine the strategies of principals in Madrasahs, to determine the level of work discipline of teaching personnel in Madrasahs, to determine the strategies of principals in increasing the discipline of teaching personnel in Madrasahs, to describe improvement steps in improving the discipline of teaching personnel in Madrasahs. The literature review used to analyze the results of this study, namely the strategy and principal and discipline of the workforce of education and the strategy of the Principal in improving the discipline of teaching workforce. The method used in this research is descriptive-analysis using a qualitative approach, data collection techniques with the stages of observation, interviews and documentation. Data analysis procedures, namely data reduction, data presentation, drawing conclusions. The results of the study, the principal's strategy in improving the work discipline of education personnel in Madrasahs by giving examples of good character traits, providing motivation, giving reward and punishment, making rules of order, developing performance. Steps to improve the principal in improving discipline in the workforce of education in Madrasahs by means of motivating members, members of study permits, providing basic disciplinary training, member reward and punishment, the use of information technology. In conclusion, the strategy to improve the work discipline of education personnel at MTs Negeri 2 Medan is by giving examples of good character traits, providing motivation, giving rewards and punishments, making rules of order, developing performance.